Trajetória e perfil do aglomerado de empreendimentos no campo odontológico: o caso do munícipio de Araraquara - Souza, Carla Daniela Molina Dalboni de (2024)
The municipality of Araraquara is nationally recognized in the field of Dentistry, mainly due to the presence of the School of Dentistry (FOAr) at São Paulo State University "Júlio de Mesquita Filho" (Unesp), founded in 1923. Over the years, the institution has played a fundamental role in the training of dentists while also providing support for cutting-edge research in the field of Dental Sciences. Additionally, the increasing number of educational institutions and courses in the dental area in Araraquara has stimulated sector growth. This tradition, coupled with academic excellence and accumulated experience, has historically fostered the creation of a large number of new ventures, beyond dental clinics, also encompassing the production and commercialization of products and services for the dental field. It is an entrepreneurial environment that, however, lacks mapping and characterization. This is precisely the motivation for conducting this research, which aims to outline the main segments of entrepreneurship in Dentistry in the municipality of Araraquara, with a view to eventually characterizing the municipality as a Local Productive Arrangement (APL). The methodological trajectory of this research can be summarized as a qualitative, exploratory, and descriptive approach, outlined as a single case study. The main data collection instruments include documentary research and direct observation. Data were analyzed using simple descriptive statistics and content analysis. The results demonstrate that although it cannot yet be classified as an APL, the municipality of Araraquara has the potential to move in this direction and could benefit from the policies and resources made available by the APLs Promotion Program, strengthening the dental segment in the municipality.